A NEW SCIENCE PROGRAM IN THE MAKING. - Davis, Ira C. (Science Education, 1939)
The article discusses the construction of a program in science education that will function in both large and small schools. The program must be promoted by an organization in which teachers have confidence and respect. A committee is formed to direct the general plans of developing the program. The factors taken into consideration in the selection of the members of the committee include the breadth of experience in the teaching of science, number of teachers to be reach for discussions and reactions and freedom to attend committee meetings on school time.